KKNI DALAM KURIKULUM BERBASIS LEARNING OUTCOMES - Imroatus Solikhah (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
This article, for all intents and purposes, is to describe the Competency-Based Curriculum in respons to the advent of National Qualification Framework (KKNI) that sets Outcomes-Based Curriculum in a wide range of education practices.  The objectives of the article are to persuit the nature of competency and the learning outcomes delineated in the KKNI clarifying some terms that are still confius. Concepts of curriculum design pertaining to development of needs analyis are briefly discussed.  In addition, a substantial discussion on the learning outcomes, core competency, competency, and objectices from where curriculum development is based upon is outlined.  In the perspective of Indonesian policy, Competency-Based Curriculum will be no longer implemented as the advent of KKNI would give great impact on the Outcomes-Based Curriculum.